VARIASI KANDUNGAN LOGAM BERAT TEMBAGA (Cu) PADA KAWASAN EKOSISTEM MANGROVE DAN KORELASINYA DENGAN KERAPATAN MANGROVE DI WILAYAH PESISIR SEMARANG DAN DEMAK - Hastuti, Endah Dwi (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2014)
Information concerning the distribution of heavy metal concentration in coastal area is needed to be observed as early indication of environment pollution. Among heavy metal pollution existed in coastal area, Copper (Cu) is one of the most utilized in anthropological and industrial activities. Most of pollutant disposed from land activities are accumulated in coastal area such as mangrove ecosystem. This research aimed to study the distribution of heavy metal Cu in the sediment of mangrove in Semarang and Demak coastal area; to study the polution level of Cu in mangrove sediment; and to analyze the correlation of mangrove abundance and concentration of Cu in the mangrove sediment. The research was conducted through observation involving 2 location: Semarang and Demak with 4 sampling station on each location and 3 sampling points at each stations. Observation variables including abundance of mangrove tree, sapling and seedling and concentration of Cu in the mangrove sediment. Analysis was conducted through correlation analysis. The result showed the abundance of mangrove tree ranged from 1,633 – 5,600 stands/ha; sapling ranged from 133 – 28,000 stands/ha; and seedling coverage ranged from 0.83% - 60.33%. while the concentration of Cu in the sediment was ranged from 5.761 – 31.241 mg/kd. The concentration of Cu in the sediment did not exceed the standart quality recommended by US-EPA (2004) with 49.98 ppm as minimum concentration of polluted sediment. The statistical analysis conducted through correlation showed there were negative correlation of mangrove tree and sapling to concentration of Cu sedimen with correlation coefficient of -0,517 (P < 0,05) and -0,756 (P < 0,05), while coverage of mangrove sapling has possitive correlation to concentration of Cu sediment with correlation coefficient of 0,233 (P < 0,05).